Portraits of prominent Greeks in the U.S.A. - Μπαστιάς, Ιωάννης Κ., 1936- ([s.n.], 2010)
The American Hellenic Institute Foundation (AHIF) is pleased to intoduce the release of a new publication Portraits of Prominent Greeks in the U.S.A. It is the first comprehensive and up-to-date presentation of 63 extraordinary individuals who share not only a Greek heritage, but also the same passion to fulfill their ambitions.